Unexpected complexation of allylpseudothiohydantoin hydrochlorides towards CuX (X = Cl, NO3, ClO4, BF4, 1/2SiF6). The first known examples of joint CuI(Cl, ClO4) and CuI(Cl, BF4) π-complexes. Issue 5 (4th March 2017) - Fedorchuk, A. A.; Kinzhybalo, V. V.; Slyvka, Yu. I.; Goreshnik, E. A.; Bednarchuk, T. J.; Lis, T.; Mys'kiv, M. G.
Abstract: By means of alternating current-electrochemical synthesis starting from a mixture of 2-imino-3-(prop-2-en-1-yl)-1, 3-thiazolidin-4-one (3-allylpseudothiohydantoin, napt) and 2-allylamino-1, 3-thiazol-4(5 H )-one (allylaminopseudothiohydantoin, aapt) hydrochlorides and corresponding copper(II) salts five new π-complexes, [Cu(napt)Cl] (1 ), [Cu2 (aapt)2 Cl]NO3 (2 ), [Cu2 (aapt)2 Cl]BF4 (3 ), [Cu2 (aapt)2 Cl]ClO4 (4 ) and [Cu2 (aapt)2 Cl]2 SiF6 ·2H2 O (5 ), were obtained and studied by X-ray single crystal diffraction and IR-spectroscopy. Napt and aapt molecules are selectively coordinated to Cu + depending on the anion type. In crystals of1 and5, the organic ligands are attached to the metal in a chelating N, (C=C)-bidentate mode. The aapt molecule in2 -4 acts as a tridentate chelating ligand, being coordinated to the copper(I) ion through the heterocyclic N atom, carbonyl O atom, and C=C bond of allyl group, forming an original cationic [Cu2 (aapt)2 Cl] + fragment with both a bridging Cl – ion and O atom of the C=O group. In the presence of the doubly charged SiF6 2– anion, Cu(I) in5 prefers to be bonded with two bridging Cl – ions, rather than the C=O group, causing [Cu2 (aapt)2 Cl] + units to associate into the infinite cationic chains. Crystals of3 and4 are the first known examples of the simultaneous BF4 – /Cl – or ClO4 – /Cl – participation in copper(I) π-complex formation. Abstract :